Ticks and tick-borne diseases in the northern hemisphere affecting humans - Boulanger, Nathalie; Iijima, Hayato; Doi, Kandai; Watari, Yuya; Kwak, Mackenzie; Nakao, Ryo; Wikel, Stephen (Frontiers in Microbiology, 2025)
Temperate zones of the northern hemisphere are increasingly impacted by human biting ticks and the human pathogens they transmit. The relationships among ticks, hosts, and pathogens are undergoing significant changes with consequences for human health. This northern hemisphere focused review examines human biting ticks and the disease causing agents they transmit as increasing public health threats due to geographic range expansion, increasing size of tick populations, emergence of newly recognized pathogens, introduction of invasive tick species that are resulting in part from changing weather patterns, land use modifications, biodiversity loss, and human activities/behaviors; all of which result in significant challenges for tick control and disease prevention. As a result of these evolving interactions and the resulting threats they pose, there exist critical needs to implement existing and develop novel tools and strategies to prevent tick bites, control tick populations, and reduce transmission of tick-borne pathogens. Timely, up to date knowledge of which ticks and tick-borne infectious agents are present within an area is foundational for physicians, public health authorities tasked with disease prevention, and the public. Achieving these objectives poses significant challenges. Here, we examine current medically important tick – host - pathogen relationships in Asia, Europe, and North America.